Soil Microarthropods as Tools for Monitoring Soil Quality: The QBS-ar Index in Three European Agroecosystems - Filippo Gallese; Laura Gismero-Rodriguez; Anton Govednik; Laura Giagnoni; Erica Lumini; Marjetka Suhadolc; Francesco Primo Vaccari; Anita Maienza (Agriculture)
The QBS-ar, based on the study of microarthropod community structure, is well known as a quick and low-cost indicator to monitor soil biological quality at the farm scale. Temperature fluctuations and other climate factors in European countries may indirectly influence soil microarthropod communities by altering resource availability and microhabitat conditions. In the context of the climate crisis, along with drought and erosion threats, especially in southern Europe, it is essential to define the limits and advantages of the QBS-ar index. We applied the QBS-ar index along a warm temperature gradient at three long-term experimental sites. Our results underlined that the QBS-ar is very sensitive for detecting soil quality and treatment effects. The results suggest that the choice of sampling season is a particularly vulnerable phase, especially for southern Mediterranean sites. Air temperature and cumulative precipitation, even in the months prior to sampling, are critical factors to consider when applying the QBS-ar index in European countries. Drought periods can negatively influence the results for soil microarthropod relative abundance; however, the presence of biological forms seems to provide useful information about the effects of treatments on soil quality. This paper lays the groundwork for scaled-up QBS-ar applications considering soils and several environmental characteristics of agroecosystems in Europe. The work can contribute to the development of applications of the index, facilitating and improving the monitoring of soil biology at the field scale. Furthermore, this study can open future perspectives for the application of QBS-ar on a larger scale thanks to the implementation and updating of an open-source database.